Evaluating Real-World Adherence and Effectiveness of the "Reboot Online" Program for the Management of Chronic Pain in Routine Care. Issue 8 (17th March 2021) - Lim, Derek Z; Newby, Jill M; Gardner, Tania; Haskelberg, Hila; Schultz, Regina; Faux, Steven G; Shiner, Christine T
Abstract: Objective: Chronic pain is a prevalent and disabling condition. Reboot Online was developed as a multidisciplinary and widely accessible online treatment program for chronic pain. It has been shown to be effective in clinical trials, but the effectiveness of this program in routine care settings remains unknown. This study aimed to examine program adherence and effectiveness in a real-world sample of participants completing Reboot Online in the community. Design and subjects: A retrospective cohort study was conducted using real-world data from participants referred the Reboot Online program by clinicians as part of their routine care, from April 2017 to April 2019. Methods: Routinely collected data on program adherence, participant demography and clinical outcomes were included in the analyses. Measures included the Pain Self Efficacy Questionnaire, Brief Pain Inventory, Tampa Scale of Kinesiophobia, Pain-Disability Index, and Patient Health Questionnaire 9-item (depression). Logistic regression was used to investigate whether certain factors predict program adherence (completion versus noncompletion), and linear mixed models were used to examine effectiveness. Results: In total, 867 participants were included in the analyses, and 583 engaged with at least one Reboot Online lesson. Of these, 42% (n = 247) completed the course in its entirety, with rurality and lower Tampa scores being significant predictors of adherence. Completers demonstrated significant improvements across all outcome measures (effect sizes ranging from 0.22 to 0.51). Conclusions: Reboot Online is an effective treatment for chronic pain in the routine care setting. Adherence was variable (overall 42%), and could be predicted by rurality and less fear of movement at baseline.